Provision of health and dental care in two middle income Asian countries - Che Musa, Muhd Firdaus; Hassan, Yang Rafidah; Rahman, Farina; Jeenia, Fatiha Tasmin (Deneysel, Biyoteknolojik, Klinik ve Stratejik Sağlık Araştırmaları Derneği |, 2018)
The purpose of this research paper is to present an overview of medical and dental care in two middle income countries: Malaysia (upper middle-income) and Bangladesh (lower middle-income). Malaysia is one country located in the South-East Asian region, consist of three territories and thirteen states which practices parliamentary democracy where the Prime Minister leads the government along with a constitutional monarch. Whereas, Bangladesh is sited at South Asian region situated by the scintillating Bay of Bengal and have both the President and Prime Minister to lead its unitary parliamentary republic. Both country has Islam as their official religion, and it is predominantly a secular country where the multicultural society lives harmoniously and free to practice their belief. This paper allow comparisons of health system which employ major influence on the public and on policy makers to promote accountability. The first part of the research paper will focus on the socio-demographic profile of both countries; this including organisation and governance of health care systems across countries while the second part will appraise and compare financial support, health manpower and delivery concerning universal coverage of health services. Finally, summary of abovementioned discussed issues.